Vocational Life Skills Learning Management In Fostering Entrepreneurial Behavior In Deaf Children At SMALB - Khaer, Abu; Wasliman, IIm; Hanafiah, Hanafiah; Dede Khaeriah, N (International Journal of Educational Research & Social Sciences, 2025)
In this age of globalization, the importance of a quality education must become a foundation. By attaining a desirable education level, job opportunities could be expanded in a competitive era, a feat that is currently difficult for all communities, including high school graduates from special needs schools. In order to provide the social right for people with disabilities, as well as their civil right, and as a solution to prepare human resources, one of the school's programs should prepares its graduates to compete in this society's workforce. This study's objective is to comprehend how "Learning Management vocational life skills to nurture the entrepreneurship behaviour of deaf children in special needs senior high school" is implemented at Special Needs Senior High School Kemala Bhayangkari in Gresik and at Special Needs Senior High School Gedangan in Sidoarjo. This research describes and analyses (1) planning (2) organizational (3) implementation (4) assessment in vocational life skills in light of GR Terry's "POAC" management theory. This research uses qualitative methodology with descriptive analysis, observational data collection, interviews, and a documentation study to validate research results. This study indicated that in the planning phase of vocational learning skills, standard curriculum is referred to. Meanwhile, the primary responsibility and function of the organization is to become an important organizational learning standard. In the stage of implementation, entrepreneurship becomes the primary criterion for creativity skills, with the aim of encouraging and motivating students to gain the confidence to work in society. Performance assessment and learner potential analysis comprise the evaluation of learning. The obstacle encountered in the vocational learning process is the society's limited awareness of the potential of high school graduates, which is supported by the opportunity to participate in Small and Enterprise Business. Solution requires an approach to SME business sectors, society, social business sectors, and government. With the conclusion of the result, all deaf learners mapped align with the student's carrier pattern as well as their creativity class potentiality; consequently, the assessment result will have a significant impact on the entrepreneurial success of the student.